2007
DOI: 10.1021/jf0704716
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anthocyanins in the Sprouts of Buckwheat

Abstract: The anthocyanin profiles and varieties/breeding line differences of anthocyanin concentrations in common/tartary buckwheat sprouts have been studied. Four anthocyanins, cyanidin 3-O-glucoside, cyanidin 3-O-rutinoside, cyanidin 3-O-galactoside, and cyanidin 3-O-galactopyranosyl-rhamnoside, were isolated from the sprouts of common buckwheat, were separated using high-performance liquid chromatography (HPLC), and were identified using reversed-phase liquid chromatography (LC)/electrospray ionization-mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 15 publications
1
61
2
Order By: Relevance
“…Cyanidin 3-O-rutinoside is the main compound that may contribute to the red color of tartary buckwheat sprouts. 31,32 Blue light induces the accumulation of anthocyanins, which play a major role in antioxidant activity. 33 All of these reports help to explain the reddish hypocotyl appearance and anthocyanin detection in blue-LED-grown sprouts described in this study.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Cyanidin 3-O-rutinoside is the main compound that may contribute to the red color of tartary buckwheat sprouts. 31,32 Blue light induces the accumulation of anthocyanins, which play a major role in antioxidant activity. 33 All of these reports help to explain the reddish hypocotyl appearance and anthocyanin detection in blue-LED-grown sprouts described in this study.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Stems, petioles, leaf veins and anthers of the wild type usually contain red or slightly red hues because of the accumulation of cyanidinbased pigments (Watanabe 2007, Kim et al 2007). Mutation of the gs1 locus results in substantial reduction in the anthocyanin content of these organs.…”
Section: Discussionmentioning
confidence: 99%
“…Four kinds of anthocyanins have been recognized in common buckwheat: cyanidin-3-galactoside, cyanidin-3-glucoside, cyanidin-3-galactopyranosyl-rhamnoside and cyanidin-3-rutinoside (Kim et al 2007). Three HPLC peaks that included these four anthocyanins were detected in the seedlings of 'Hitachi Akisoba' (Fig.…”
Section: Hplc Analysis Of Anthocyaninsmentioning
confidence: 99%
“…Some studies found that flavonoids from buckwheat sprouts have anti-stress effects and anti-inflammatory in mice and in vitro (Ishii et al 2008;Watanabe and Ayugase 2008). Additionally, Kim et al (2007a) identified some anthocyanins in the sprouts of common and tartary buckwheat sprouts. Watanabe (2007) evaluated the contribution of anthocyanin compounds of commercial buckwheat sprouts to antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%